Study on costing techniques in Germents sector of Bangladesh: SME Sweaters Limited as a case - Sarker, Md. Al-Amin (BRAC Business School, BRAC University, 2012)
The Merchandising department is the most important part of the export oriented business. It increases the opportunity for entrepreneurship development in garment sector. Thus it helps the unemployed people as well as the government to remove unemployment problem and also play an important role in the economic development of the country. I have worked there three months as requirement of the internship phase of BBA program under the BRAC Business School. My topic is Costing Techniques in Garments Sector of Bangladesh: SME Sweaters Limited as a Case. This Report is originated as a partial requirement of BBA program. In order to achieve perfect garment costing, one must know about all the activities including purchase of fabrics, sewing, packing, transport, overheads, etc and also about their costs, procedures, advantages and risk factors. The Bangladeshi apparel industry is very large and diverse, employing 6 million people and accounting for 87 per cent of the country's exports. The apparel industry plays a pivotal role as a key driver of the national economy and has grown to be the most significant contributor to the country's economy over nearly three decades of its existence. However, during last 10 years, the industry's actions, government policies as well as market events have begun to converge, providing several growth opportunities for the sector domestically as well as in the global market. As the MFA quota-regime ended, Bangladesh presented many opportunities for buyers, suppliers and investors to collaborate with its textile industry, and to profit from the partnership. While the industry recorded a remarkable growth in a protected market environment, it faces a series of challenges that have come to the fore in the post-quota situation, notably in areas such as: 􀂃 Price competitiveness. 􀂃 Faster lead times. 􀂃 High raw material base. 􀂃 Full service offering.